Protective Effects Oncorneal Endothelium During Intracameral Irrigation Using N-(2)-l-alanyl-l-Glutamine - Jin, Mengyi; Wang, Yanzi; Wang, Yixin; Li, Yunpeng; Wang, Guoliang; Liu, Xuezhi; Xue, Yuhua; Liu, Zuguo; Li, Cheng (Frontiers in Pharmacology, 2020)
Corneal endothelial disease is a global sight-threatening disease, and corneal transplantation using donor corneas remains the sole therapeutic option. A previous work demonstrated that N (2)-alanyl-glutamine (Ala-Gln) protected against apoptosis and cellular stress, and maintained intestinal tissue integrity. In this pursuit, the present study aimed to examine the effect of Ala-Gln in the protection of the corneal endothelium and expand its range of potential clinical applications. Mice in the control group were intracamerally irrigated with Ringers lactate injection, whereas those in the experimental group were irrigated with Ringers lactate injection containing Ala-Gln. The mean intraocular pressure increased to 44±3.5 mm Hg during intracameral irrigation (normal range: 10.2 ± 0.4 mmHg). In vivo confocal microscopy results showed that the addition of Ala-Gln protected the morphology, structure and density of the corneal endothelial cells. Optical Coherence Tomography (OCT) measurements showed that corneal thickness was not significantly different between the two groups, because of the immediate corneal edema after irrigation, but the addition of Ala-Gln obviously promoted the recovery of the corneal edema. Scanning electron microscopy indicated that the corneal endothelial cells were severely ruptured and exfoliated in the Ringer’s group accompanied with cellular edema, when compared with the Ala-Gln group. The intracameral irrigation using Ala-Gln protected the structure and expression of cytoskeleton and Na-K-ATPase, which exhibited a regular distribution and significantly increased expression in comparison to Ringer's group. Furthermore, Ala-Gln maintained the mitochondrial morphology and increased the activity of mitochondria. Moreover, transmission electron microscopy showed that intracameral irrigation of Ala-Gln reversed the ultrastructural changes induced by the acute ocular hypertension in mice. Our study demonstrates that the intracameral irrigation of Ala-Gln effectively maintained the corneal endothelial pump function and barrier function by protecting the mitochondrial function and preventing the rearrangement of cytoskeleton in acute ocular hypertension in mice.